2008
DOI: 10.1002/ajh.21239
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis stimulating agents are associated with reduced survival in patients with multiple myeloma

Abstract: The impact of erythropoiesis-stimulating agent (ESA) on cancer patients' survival has recently become a matter of extensive discussion. Studies in solid tumors demonstrated that ESA adversely affects survival. This issue has not been sufficiently studied in patients with multiple myeloma. In this study, which included 323 multiple myeloma patients followed in our Institution between 1988 and 2007, we demonstrated by using a proportional hazards model including multiple covariates (age, LDH, Hb, platelets, seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…6,10,11 The hepcidin levels correlated negatively with hemoglobin, indicating that hepcidin could be causal in the anemia of MM. In addition, our cellular reporter system also displayed higher hepcidin promoter activity after treatment with serum of MM patients, compared with serum from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,10,11 The hepcidin levels correlated negatively with hemoglobin, indicating that hepcidin could be causal in the anemia of MM. In addition, our cellular reporter system also displayed higher hepcidin promoter activity after treatment with serum of MM patients, compared with serum from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a study evaluating 34 MM patients at diagnosis or recurrence, Katodritou et al similarly demonstrated that patients' serum hepcidin levels were elevated and inversely correlated with hemoglobin concentrations. 11 Using Hep3B cells in vitro, we showed that treatment with MM patients' sera induced hepcidin mRNA expression more than healthy sera, and that with some samples, hepcidin induction was abrogated by neutralizing anti-IL-6 antibodies. 6 However, for other sera, the antibodies had no effect, suggesting that additional serum factors can induce hepcidin expression.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…A retrospective study of 257 patients with multiple myeloma has recently demonstrated that ESAs are associated with improved overall survival in anaemic patients at Southwestern Oncology Group stages II, III and IV [hazard ratio (HR) 0AE6; 95% confidence interval (CI) = 0AE38-0AE94] (Baz et al, 2007). In contrast, another retrospective assessment of 323 myeloma patients treated with ESAs and followed up between 1988 and 2007 has shown their shorter survival (31 vs. 67 months; P < 0AE001) and median progression-free survival (14 vs. 30 months; P < 0AE001) compared to untreated patients (Katodritou et al, 2008). However, this study has important limitations in its design, especially because of baseline differences between the two groups in the most important prognostic factors for multiple myeloma (higher age, higher International Staging System stage, lower platelet count, haemoglobin levels, serum albumin, higher serum creatinine, lactate dehydrogenase and b2-microglobulin in the ESAs group), as well as in disease stage and lines of treatment .…”
Section: Esas In the Treatment Of Anaemia In Cancer Patientsmentioning
confidence: 99%